Facile synthesis of a 3-deazaadenosine phosphoramidite for RNA solid-phase synthesis - Mairhofer, Elisabeth; Fuchs, Elisabeth; Micura, Ronald (Beilstein Journal of Organic Chemistry, 2016)
Access to 3-deazaadenosine (c3A) building blocks for RNA solid-phase synthesis represents a severe bottleneck in modern RNA research, in particular for atomic mutagenesis experiments to explore mechanistic aspects of ribozyme catalysis. Here, we report the 5-step synthesis of a c3A phosphoramidite from cost-affordable starting materials. The key reaction is a silyl-Hilbert–Johnson nucleosidation using unprotected 6-amino-3-deazapurine and benzoyl-protected 1-O-acetylribose. The novel path is superior to previously described syntheses in terms of efficacy and ease of laboratory handling.
Keywords: deazapurine nucleoside; nucleosidation; protection groups; ribozymes